Pemanfaatan Wondershare Quiz Creator Dalam Tes Berbasis Komputer - Haida Dafitri (Program Studi Sistem Informasi, 2017)
Designing test items manually done by the teachers of SMA Harapan I Medan isn’t effective and effeciency. It is proved by the teachers who collected answering test late. It is happened because a teacher in the certain field makes test items with various types in a short time. Beside an uneffective and unefficient time, it is seen many papers’ distribution not only for test items with various types but also students’ answering which is prepared by the school and there is students’ amnipulating in doing examination. In solving this problems in the school and developing technology, the school comitee wants to change test system manually to be computerized. It means that the students do using computer (computer based test) by using wondershare quiz creator application. Wondershare Quiz Creator is an aplication which is used in making online test (electronic test) by upload test in a website and the users are able to do test in web by using computer connected by the internet